A influência das políticas públicas de habitação rural no modo de vida tradicional: um estudo sobre o Programa Melhorias Habitacionais para controle da doença de Chagas na comunidade quilombola Brejo dos Crioulos/MG - Érico de Oliveira e Silva (2020)
The aim of this research is to discuss the impact of public policies that involve the construction of housing in the contemporary context of traditional Brazilian peoples and communities, applied to the quilombo Brejo dos Crioulos, located on the banks of the Arapuim River, at the left bank of the Verde Grande River, on the border of the cities of São João da Ponte and Varzelândia, in the north of Minas Gerais. The research was conducted through a bibliographic review, seeking to cover elements that define traditional culture, its socioeconomic and territorial context, in addition to the critical analysis of the documentation related to the implementation of public policies, with regard to interventions in the built space of the houses from the “Housing Improvement Project for the Control of Chagas Disease” (PMHCDC), under the responsibility of the National Health Foundation (FUNASA), linked to the Ministry of Health of the Federal Government. FUNASA’s policy proposes the construction of new houses with materials from the construction industry replacing the traditional quilombola house aiming at the control of chagas disease. We understand that the material and cognitive processes involved in vernacular building, as well as its own occupation, are part of the traditional way of life of this group and that the house in the quilombola territory involves traditional constructive techniques and unconventional knowledge, which are part of its counter-colonial condition of territorial resistance. The study is based on the discussion about the need to develop specific public policies for quilombola communities, based on the relations of value and meaning between cultural heritage, vernacular architecture, and traditional way of life. Likewise, this research discusses alternative actions compatible with the notion of sustainable development that are part of the social technologies critical theory and of the concept of formal-material. Thus, this investigation sought to understand the impact of public policy on traditional ways of living and occupying the territory, questioning its scope and impact, which exposes the vulnerability of these communities to the destruction of their memory and the epistemicide of their counter-colonizing knowledge.